Mengintegrasikan Kecintaan Budaya Lokal dan Moderasi Beragama melalui Kurikulum Muatan Lokal - Listiyani Siti Romlah; Zahra Rahmatika; Rahmad Purnama; Istiazah Ulima Hakim (Kopertais Wilayah XV Lampung, 2023)
This journal explores the integration between building love for local culture and promoting religious moderation through the implementation of the Local Content Curriculum. This study aims to highlight the importance of incorporating local cultural values and religious teachings into the curriculum to shape students' appreciation of their cultural heritage and promote a balanced understanding of religious practices. This type of research is descriptive qualitative research, using interviews, observation, and documentation, as well as questionnaires, to test the effectiveness of the integration of these elements in the local content curriculum and its impact on students' attitudes towards local culture and religious tolerance. The findings of this research contribute to the discussion on curriculum development by emphasizing the importance of strengthening cultural identity and encouraging the harmonious life of diverse religious beliefs in educational settings. This study concludes with recommendations for education policymakers and curriculum developers to enhance local cultural integration and religious moderation through local content curricula, promoting a holistic educational approach that celebrates cultural diversity and religious harmony.